2013
DOI: 10.1128/aem.02911-12
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Reduction of Cell Viability and Enhanced Matrix Production in Pseudomonas aeruginosa PAO1 Flow Biofilms Treated with a d -Amino Acid Mixture

Abstract: bTreatment of Pseudomonas aeruginosa PAO1 flow biofilms with a D-amino acid mixture caused significant reductions in cell biomass by 75% and cell viability by 71%. No biofilm disassembly occurred, and matrix production increased by 30%, thereby providing a thick protective cover for remaining viable or persister cells.T he multifactorial tolerance of surface-attached complex microbial communities known as biofilms apparently renders conventional treatment strategies ineffective. Biofilms persist and are hard t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…The uniformly vertical orientation of hyphae in most of the upper region of a/␣ biofilms formed in RPMI medium versus the less uniformly oriented hyphae in a/␣ biofilms formed in Spider medium, and the spaces in calcofluor white-stained biofilms formed in Spider medium that were absent from biofilm formed in RPMI medium, suggested to us that a difference may exist in matrix deposition between the two biofilms. To assess matrix density, we stained fixed preparations of a/␣ biofilms formed in the alternative media with Sypro Ruby, a general protein stain (35), which has previously been used to stain a variety of biofilm matrices (36)(37)(38)(39). This stain was not differentially sequestered at the top of biofilms, as was calcofluor white.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The uniformly vertical orientation of hyphae in most of the upper region of a/␣ biofilms formed in RPMI medium versus the less uniformly oriented hyphae in a/␣ biofilms formed in Spider medium, and the spaces in calcofluor white-stained biofilms formed in Spider medium that were absent from biofilm formed in RPMI medium, suggested to us that a difference may exist in matrix deposition between the two biofilms. To assess matrix density, we stained fixed preparations of a/␣ biofilms formed in the alternative media with Sypro Ruby, a general protein stain (35), which has previously been used to stain a variety of biofilm matrices (36)(37)(38)(39). This stain was not differentially sequestered at the top of biofilms, as was calcofluor white.…”
Section: Resultsmentioning
confidence: 99%
“…Sypro Ruby is a general protein dye (35) that has been extensively used for staining the matrix of fixed bacterial biofilms (36)(37)(38)(39). A comparison of matrix staining with calcofluor white, a chitin stain (25), was less effective because of the trapping effect at the top of both types of biofilms during staining.…”
Section: Discussionmentioning
confidence: 99%
“…Others found that specific D-amino acids disrupted Pa biofilms and were particularly effective when combined with antibiotics (86). When used alone, however, treatment of Pa biofilms with a mixture of D-amino acids induced ϳ30% increase in matrix production, thereby suggesting the potential to inadvertently provide protection for any remaining viable or persister cells (86). Recently, Leiman et al (87) indicated that D-tyrosine actually inhibited bacterial growth, and others have not found Damino acids to be effective (88).…”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%
“…In contrast to their planktonic counterparts, biofilm-derived bacteria have a distinctive phenotype regarding metabolic activity and gene expression, conferring an inherent resistance to antimicrobial agents as well as mechanisms of host clearance and making the treatment of biofilm-associated infections extremely difficult [2]. Biofilms persist and are hard to eradicate because of mechanisms that involve the restricted penetration of antimicrobials, differential physiological activity, and the presence of phenotypic variants and persisters, efflux systems, and enhanced repair systems [3]. Resistance is often genetically inherited and therefore transmitted progeny of bacterial colonies, or it can be acquired through horizontal gene transfer [4].…”
Section: Introductionmentioning
confidence: 98%
“…Since D-amino acids are synthesized and released by many bacterial species, including the opportunistic human pathogen P. aeruginosa, and have been shown to lack significant toxicity, the idea of using them to combat biofilm-associated infections is highly attractive [3]. Peptidoglycan (PG) is the major component of the bacterial cell wall and the most commonly cited source of D-amino acids in bacteria.…”
Section: Introductionmentioning
confidence: 99%